PENGEMBANGAN BUKU AJAR BAHASA INDONESIA BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN KETERAMPILAN MENULIS ILMIAH MAHASISWA FARMASI - Wahyuni, Sinta; Amna, Fitra Afrida (STKIP Pesisir Selatan, 2025)
This study aims to develop an Indonesian language textbook using the Contextual Teaching and Learning (CTL) approach to improve the scientific writing skills of pharmacy students. The research adopted the Four-D development model (Define, Design, Develop, and Disseminate). Needs analysis was conducted using questionnaires, interviews, and document studies to identify students’ initial conditions, obstacles, and expectations regarding academic writing. Findings revealed that while students understood the basic structure of scientific writing, they struggled to organize ideas, apply proper citation, and transform laboratory reports into systematic articles. The design stage produced a prototype consisting of 17 chapters, of which 14 were validated as relevant and 3 were excluded. The prototype was subsequently validated by experts in materials, media, and language. Novelty: This research provides novelty by integrating CTL principles into a Bahasa Indonesia textbook specifically tailored to pharmacy students, ensuring meaningful, practical, and contextual learning outcomes.